Kajian Terhadap Makna “Boboso” Dalam Tradisi Lisan Masyarakat Maluku Utara Dalam Perspektif Analisis Pragmatics Kritis - Djafar, Hariyanti; Ismail, Julia (Jurnal Ilmiah Wahana Pendidikan, 2023)
Boboso is part of an oral tradition that is still frequently used and trusted for its truth among rural and urban communities in North Maluku province. Boboso, which usually begins with the words "don't" or "shouldn't" is a meaningful sentence and is strictly avoided in its implementation by speakers and listeners in North Maluku. This research uses a descriptive qualitative approach with critical pragmatic analysis methods and library research studies, namely by reviewing scientific literature. Library research in this study aims to provide scientific comparison material to interpret the implied meanings of the prohibition and boboso sentences. This research also involved in-depth interviews with community informants spread across North Maluku Province and analyzed from a critical pragmatic perspective. The results of this research explain that every prohibition sentence contains an element of advice in perspective; health, adjustment to economic conditions for survival, as well as historical elements. Prohibition and boboso sentences are not just oral traditions passed down from generation to generation, but can be studied from an academic and empirical perspective so that their implementation can be understood in terms of their implied meanings. Furthermore, the advice content in these sentences called boboso can be recommended as teaching material in formal schools and universities as part of character education based on local content.